The coverage of talk shows on corruption issues and audience attitudes towards them: A comparative study of "Al-Hekaya" and "Ala Mas’ouliyati" - Elrahman, Mahmoud Gamal Sayed Abd; Hammad, Ahmed Samir; Abdou, Khaled Mohamed Salah (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates Egyptian talk shows’ treatment of corruption issues and audiences’ opinions and actions regarding that coverage. The study evaluates the impact these programs have had on the culture of corruption by comparing two leading programs, Al-Hekaya and Ala Mas’ouliyati, to determine where both fit within the broader spectrum of public dialogue on corruption. Analyzing program effectiveness, media framing strategies and audience trust in the presented narratives, this study applies content analysis and audience surveys. Corruption news and the mode of talk shows have greatly influenced the opinion of the people on corruption although there are many factors such as media owners and political followers and editorial policies that tend to be there. But how these programs frame and present the material can affect audience trust and engagement with corruption cases. Nonetheless, there are also differences in viewer reliance on television as a primary information source, and these relate to demographic and socio-economic differences, as the study also indicates. Through an analysis of the role of televised discussions within the wider media ecosystem, this study highlights the potential of independent journalism, and freedom of the media, when it comes to increasing transparency and holding the government accountable. These results have implications for debates around whether the media can combat corruption and promote civic participation.